New kid eaudiobook - Craft, Jerry (2019)
2020 Audie Awards® Finalist—Middle Grade Winner of the Newbery Medal, Coretta Scott King Author Award, and Kirkus Prize for Young Readers' Literature, and an Audie Award finalist! An original full-cast audio adaptation of the graphic novel from award-winning author-illustrator Jerry Craft, performed by the author with Jesus Del Orden, Nile Bullock, Robin Miles, Guy Lockard, Peyton Lusk, Rebecca Soler, Dan Bittner, Phoebe Strole, Marc Thompson, Miles Harvey, and Ron Butler. Named an Audible Best Audiobook of the Year! Perfect for fans of Raina Telgemeier and Gene Luen Yang, New Kid is a timely, honest novel about starting over at a new school where diversity is low and the struggle to fit in is real. Seventh grader Jordan Banks loves nothing more than drawing cartoons about his life. But instead of sending him to the art school of his dreams, his parents enroll him in a prestigious private school known for its academics, where Jordan is one of the few kids of color in his entire grade. As he makes the daily trip from his Washington Heights apartment to the upscale Riverdale Academy Day School, Jordan soon finds himself torn between two worlds—and not really fitting into either one. Can Jordan learn to navigate his new school culture while keeping his neighborhood friends and staying true to himself? Filled with sound effects and original music, this audio adventure is one the whole family will enjoy. A selection of the Schomburg Center's Black Liberation Reading List. Plus don't miss Jerry Craft's Class Act!